Disparities and Strengthening of the Authority of the DPD in the Indonesian Constitutional System - Maghfur, Asroful; Ikmal, Moh.; Syafi`i, Imam (SAINTIS Publishing, 2025)
This research is to analyze the role and function of the representative system in Indonesia from an institutional perspective can be interpreted as adhering to a soft bicameral system, that legislative power essentially has three functions, namely, legislative, supervisory and representation functions. The current state of Indonesia which claims to be bicameral in accordance with the 1945 Constitution of the Republic of Indonesia (article 2 paragraph 1), bicameral is equality between its institutions is not far apart, while in Indonesia that claims bicameralism in its implementation is not so, in accordance with laws and regulations and Constitutional Court Decisions such as Law No. 17 of 2014, Law No. 15 of 2019, DPR Regulation No. 1 of 2020 and Constitutional Court Decision No. 92/PUU-X/2012, DPD is very limited which only has the right to submit drafts and participate in discussions, the rest is dominated by the DPR, starting from submission, discussion to approval. So actually, if you look at the legislative process, Indonesia adheres to a one-chamber system (unicameral plus), because the DPD does not have a full legislative function like the DPR.